Determination the depth and thickness of the Yamama Formation using the reflection seismic method in the Nasiriyah field-Southern Iraq - Ali Kareem Jaheed (University of Thi-Qar Journal of Science, 2024)
An interpretive study of the Yamama Formation for seismic data in the Nasiriyah oil field was achieved in this work. We choice this location for our study because of its important location between several oil fields. Using SERVPRO-10, the NS-1 well data and the seismic data were represented by time, depth, velocity, thickness, and three-dimensional mapping of the thickness distribution. The seismic interpretation of the upper and lower-time maps of the Yamama Formation showed the presence of faults towards the southwest and northeast as a result of the influence of the transverse fault system. Structural features of the Yamama Formation was also  identified from the depth maps, with seven closures identified in the upper boundary and three in the lower boundary, representing the lowest occurrence of structural influence. The 3D map showed the highest value of formation thickness in the northeast direction, and that represents the distribution of formation rock units the directions of increasing sediment thickness, and the deposition location from the shelf margin to the sedimentary basin, indicates the increasing in sedimentation energy of the basin. Petrophysical properties of the Yamama Formation maps show a significant increase in the value of density and velocity and its relationship with acoustic impedance and a decrease in porosity from northeast to southwest directions